Combining shells and sequences to untangle taxonomy of abalone in Sabah, Malaysia - Mamat, Nur-Syahirah; Esa, Yuzine; Sigwart, Julia D.; Mohd Nor, Siti-Azizah; Wong, Nur Leena W. S.; Kadar, Nazia Abdul; Machado, Fabrizio Marcondes; Abdul-Halim, Siti Amalia Aisyah; Aminarrashid, Ahmad Ammar Akhyar (Frontiers Media SA, 2025)
Abalone, herbivorous marine mollusks of significant economic and ecological importance, exhibit considerable morphological plasticity. This poses a challenge for accurate species identification, which in turn could undermine the assessment of impacts from harvesting. The present study employed an integrative approach combining geometric morphometrics and DNA barcoding to address potential taxonomic ambiguities in abalone populations from Sabah, Malaysia. Especially in this megadiverse region, it could be expected that multiple species may co-occur. Morphometric analysis of 135 specimens, using 14 shell landmarks, confirmed that all individuals clustered within the Haliotis asinina group when compared with data from Haliotis glabra. This was supported by genetic analyses, which demonstrated 99% sequence similarity among novel CO1 sequences and previously published DNA barcodes from H. asinina. Despite overlapping morphological traits between H. asinina and similar congeners, the integrative approach conclusively identified all specimens as H. asinina. Although there are some limits to shell-based taxonomy, quantitative approaches to both morphological and genetic data can resolve species boundaries. These results underscore the importance of employing integrative methods in biodiversity assessments and conservation strategies for tropical abalone species.